Designing Squaraines to Control Charge Injection and Recombination Processes in NiO-based Dye-Sensitized Solar Cells - Langmar, Oliver; Saccone, Davide; Amat, Anna; Fantacci, Simona; Viscardi, Guido; Barolo, Claudia; Costa, Ruben Dario; Guldi, Dirk Michael (ChemSusChem, 2017)
Herein, the synthesis of a new family of squaraines (SQs) and their application in p-type dye-sensitized solar cells (DSSCs) is presented. In particular, two sets of SQs were designed featuring either two or four anchoring carboxylic groups combined with either oxygen or dicyanovinyl central groups. The SQs were characterized by using a joint theoretical, photophysical, and electrochemical approach. Importantly, the presence of different central groups forces a frozen cis (dicyanovinyl group) or a trans (oxygen group) SQ conformation. Based on the latter, the current work enables a direct comparison between cis and trans isomers as well as the impact of a different number of anchors. Considering their electron-accepting and light-harvesting character, they were tested in NiO-based DSSCs. Photocurrent-voltage, incident photon-to-current conversion efficiency (IPCE), and electrochemical impedance spectroscopy measurements were performed. By virtue of their different symmetry, stereochemistry, and number of carboxylic groups, altered adsorption behavior onto NiO electrodes as well as diverse charge injection and charge recombination dynamics were noted under operation conditions. SQs with four linkers in a frozen cis isomerism show the best charge collection properties among the investigated SQs, providing a valuable guideline for the molecular design of future SQs for p-type DSSCs. In addition, we assembled tandem DSSCs featuring SQ/NiO photocathodes and N719/TiO2 photoanodes. The IPCE of the resulting tandem DSSCs implies light harvesting throughout most of the visible part of the solar spectrum owing to the complementary absorption features of SQ and N719.
EAM Import::2019-03-13